Effectiveness of Tumescent in Reducing Blood Loss in Tangential Excision for Adult Burn Patients: A Systematic Review - Aditya Wardhana; Albireza Ruhimat (The Lingkar Studi Bedah Plastik Foundation and is affiliated with the Department of Plastic Surgery, Faculty of Medicine, Universitas Indonesia., 2026)
Introduction: T Tangential excision is a standard surgical approach for managing deep burns, yet it often results in considerable intraoperative blood loss. This can lead to increased transfusion needs and a higher risk of postoperative complications. Among the strategies developed to minimize bleeding, tumescent infiltration—using diluted vasoconstrictors such as epinephrine—has gained interest due to its affordability, simplicity, and applicability in resource-limited settings.Method: This systematic review followed PRISMA 2020 guidelines. Literature searches were conducted in CENTRAL, MEDLINE (via PubMed), Scopus, and EBSCOhost. Included studies comprised randomized controlled trials, cohort studies, and case series assessing the impact of tumescent infiltration on intraoperative blood loss in adult patients undergoing tangential excision. Extracted data included study design, patient demographics, burn characteristics, surgical techniques, and outcomes related to blood loss and transfusion. Risk of bias was assessed using RoB 2.0 and ROBINS-I tools.Results: Seven studies were included for qualitative synthesis, most of which were cohort designs involving patients with full-thickness burns covering 1–50% of Total Body Surface Area (TBSA). The use of tumescent infiltration—commonly employing epinephrine concentration between 1:500.000 until 1:2.000.000 dilution—consistently demonstrated reduced intraoperative blood loss compared to conventional techniques such as adrenaline-soaked gauze. The degree of blood loss reduction varied across studies, influenced by TBSA, unit used, surgical methods, and infiltration protocols.Conclusion: Tumescent infiltration using epinephrine is an effective and safe method for reducing intraoperative bleeding in adult burn patients undergoing tangential excision even though there are differences in measurement of bleeding and tumescent concentration. Further multicenter cohort studies with standardized blood loss measurements are needed to confirm these findings and support wider adoption.